1973
DOI: 10.2466/pms.1973.36.3.1007
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Disciplinary Catalogue of Uric Acid Literature of Interest to Behavioural Scientists

Abstract: The research on uric acid encompasses a large number of disciplines and their respective journals. This bibliography (1948 to 1972) was assembled to provide a co-ordinated reference to this source material for behavioural scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 130 publications
1
0
0
Order By: Relevance
“…An increasing number of research reports has indicated the existence of an association between levels of uric acid in serum (SUA) and behavioural variables such as intelligence, cognitive style, achievement motivation, and so on. For example, Stetten & Hearon (1959) found a small but statistically significant correlation between SUA levels and intelligence test scores, and this has been confirmed by other researchers (e.g. Mersy et al, 1968).…”
supporting
confidence: 77%
“…An increasing number of research reports has indicated the existence of an association between levels of uric acid in serum (SUA) and behavioural variables such as intelligence, cognitive style, achievement motivation, and so on. For example, Stetten & Hearon (1959) found a small but statistically significant correlation between SUA levels and intelligence test scores, and this has been confirmed by other researchers (e.g. Mersy et al, 1968).…”
supporting
confidence: 77%